Distribution of serotype-specific genotypes of Aggregatibacter actinomycetemcomitns in Brazilian patients with Down syndrome with different periodontal conditions - Gaetti-Jardim Júnior, Elerson [UNESP]; Sumida, Doris Hissako [UNESP]; Schweitzer, Christiane Marie [UNESP] (SciELO Agencia Nacional de Investigacion y Desarrollo (ANID), 2013)
This study evaluated the occurrence of highly or minimally leukotoxic strains of Aggregatibacter actinomycetemcomitans (Aa) from patients with Down syndrome and the distribution of the different serotype-specific genotypes of this microorganism. Sixty-seven patients with Down syndrome were subjected to dental, periodontal and radiographic evaluations. Samples of subgingival biofilm were collected and plated onto TSBV agar and characteristic colonies of A. actinomycetemcomitans were identified by biochemical methods. The occurrence of this bacterium was also evaluated directly in the clinical specimens by PCR. The presence of 530 bp deletion in the promoter region was also determined by PCR in order to evaluate distribution of highly or minimally leukotoxic strains. A. actinomycetemcomitans was detected in 11.1% by culture and 22.2% by PCR from periodontally healthy subjects, 100% of the patients with Down syndrome with aggressive periodontitis, 50% and 75% of patients with chronic periodontitis by culture and PCR respectively. Only two patients with aggressive periodontitis were colonized by highly leukotoxic Aa. Serotype-specific genotypes a and c were the most prevalent. The results suggest the role of peculiar characteristics of Aa and patients with Down syndrome in the development of periodontitis and the influence of peculiar characteristics of the population in this process.

Este estudio evaluó la presencia de cepas altamente o mínimamente toxicas de Aggregatibacter actinomycetemcomitans (Aa) de los pacientes con síndrome de Down y la distribución de los serotipos genotipos específicos de este microrganismo por cultivo y PCR. Sesenta y siete pacientes con síndrome de Down fueron sometidos a un tratamiento dental y evaluaciones clínicas. Las muestras de biofilme subgingival fueron recogidas y cultivadas en agar TSBV y colonias características de Aa fueran identificadas mediante métodos bioquímicos. La presencia de esta bacteria se evaluó también directamente en las muestras clínicas por PCR. Los aislados y las muestras clínicas también se probaron con el fin de evaluar la distribución de serotipos de genotipos específicos por PCR, mientras que la presencia de delección de 530 bp en la región promotora del gen ltxC también fue determinado por PCR con el fin de evaluar de distribución de las cepas altamente o mínimamente toxicas. Aa fue aislado en 11,1% y 22,2% por PCR de pacientes periodontalmente sanos; en todos los pacientes con síndrome de Down con periodontitis agresiva, y en 50% y 75% de los pacientes con periodontitis crónica por cultivo y PCR, respectivamente. Sólo dos pacientes con periodontitis agresiva fueron colonizados por cepas altamente tóxicas. Los serotipos y genotipos específicos a y c fueron los más frecuentes. Los resultados sugieren una asociación de las peculiares características de Aa con las características de los pacientes con síndrome de Down en el desarrollo de la periodontitis.
Distribución de los serotipos genotipos específicos de aggregatibacter actinomycetemcomitans en los pacientes brasileños con Síndrome de Down con diferentes condiciones periodontales
Keywords: Gingivitis; Bacteria; Periodontitis; Down syndrome; Gingivitis; Bacterias; Periodontitis; Síndrome de Down